Strength and seismic anisotropy of textured FeSi at planetary core conditions - Kolesnikov, E.; Kupenko, I.; Achorner, M.; Plückthun, C.; Liermann, H.-P.; Merkel, S.; Sanchez-Valle, C. (Frontiers in Earth Science, 2022)
Elastic anisotropy of iron-bearing alloys and compounds can lead to a variation of seismic velocities along different directions in planetary cores. Understanding the deformation properties of candidate core-forming materials is thus necessary to reveal the details about the interior of distant planets. Silicon has been considered to be one of the dominant light elements in the cores. Here we investigated the deformation of the ε-FeSi phase up to 49 GPa and 1100 K employing the radial X-ray diffraction technique in diamond anvil cells. Stoichiometric FeSi is a good approximation for the deformation behavior of the Fe-FeSi system and the low-pressure polymorph of FeSi may be the stable phase in the cores of small terrestrial planets such as Mercury. Yield strength in ε-FeSi is higher than in hcp-Fe and hcp-Fe-Si alloys, while the temperature has little influence on the lattice strain parameters, yield strength, and anisotropy. The azimuthal anisotropy of the longitudinal sound waves in ε-FeSi is below 0.6 % at low pressure and decreases further with compression, while the shear wave contrast is below 1.25 % in the entire investigated pressure range. Therefore, polycrystalline aggregates of iron silicide are nearly isotropic at extreme conditions. Consequently, any observed anisotropy in planetary cores will be incompatible with silicon being the dominant light element in the core composition.